Burden of Depression, Anxiety and Stress; The Psychiatric Burden in COVID-19 Patients at a Tertiary Care Hospital in Pakistan - Kakar, Muhammad Siddique; Sadiq, Noman; Rauf, Shehzad; Ahmad, Asrar; Khattak, Haroon; Awais, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the levels of depression, anxiety and stress in patients diagnosed with COVID-19.Study Design: Cross-sectional study.Place and Duration of Study: COVID isolation ward of PNS Shifa Hospital, Karachi Pakistan, from May to Jun 2020.Methodology: A total of 110 patients whose COVID-19 PCR tests were positive were selected. They had a history of at least one-week admission to the hospital, and all of them were stable or had mild symptoms. Depression, Anxiety and Stress scale (DASS 21) was administered to all the patients through a video call.Results: The study revealed that 30 (27.3%) of the COVID-19 patients had depressive features, whereas 37 (33.6%) were found to be anxious, and 13 (11.8%) were under stress during this time. Depressive features were more common in the female gender affecting 9 (56.2%) out of 16 females (p=0.011) and unemployed patients affecting 12 (54.5%) out of 22 unemployed patients (p=0.006). Anxiety was more common in the female gender affecting 11 (68.7%) out of 16 females and married patients, affecting 26 (27.6%) out of 94 married patients (p=0.01). Stress was found to be more in females, affecting 8 (50%) out of 16 females (p=0.01).Conclusion: This study showed that the diagnosis of COVID-19 can lead to psychological effects, and patients should be monitored for depression, anxiety and stress.